The Influence of Advanced Nursing Practice on Patient Care Outcomes - Al-Homrany, Sami Abdullah; Oreef, Sara Faisal M; Alansari, Reham Obaidallah Ali; Zain, Fatima Jaber; Mohammed, Fatimah Abdullah Abdulrahim; Alharbi, Rehab Saud; Almutairy, Suha Naif; Almotery, Munifa Saidan; Alotaibi, Reem Helal; Alfehaid, Salman Abdullah; et al. (Journal of Posthumanism, 2024)
This study investigated the impact of Advanced Practice Hospitalization Nurses (APHNs) on clinical outcomes and adherence to clinical practice guidelines (CPGs) in hospital settings. Using a quasi-experimental design across three public hospitals in the Saudi Arabia, the study compared intervention units (IU) with APHNs to control units (CU) without APHNs. The research focused on two key areas: pressure ulcer prevention and vascular access device management. Data was collected through 6,500 monthly audits over 12 months, involving 3,600 patients for pressure ulcer assessments and 2,700 for vascular access evaluations. Results demonstrated significant improvements in the intervention units, with CPG adherence odds 1.8 times higher for pressure ulcer care and 1.05 times higher for vascular access management compared to control units. Notable improvements included increased risk assessment compliance (from 62% to 93% in IU), reduced pressure ulcer prevalence (from 6.2% to 4.8% in IU), and decreased catheter-related adverse events (from 18% to 12% in IU). The findings suggest that incorporating APHNs into hospital units significantly enhances evidence-based care implementation and improves patient outcomes, supporting the value of advanced nursing roles in healthcare delivery.